2021
DOI: 10.1007/s00737-021-01184-7
|View full text |Cite
|
Sign up to set email alerts
|

Resilience: a mediator of the negative effects of pandemic-related stress on women’s mental health in the USA

Abstract: The role of resilience in mediating the negative effects of the COVID-19 pandemic on the mental health of US women is poorly understood. We examined socioeconomic factors associated with low resilience in women, the relationship of low resilience with psychiatric morbidity, and the mediating role of resilience in the relationship between pandemic-related stress and other coincident psychiatric morbidities. Using a quota-based sample from a national panel, we conducted a webbased survey of 3200 US women in Apri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…When people go through the adversity of COVID-19, resilience may work as a crucial factor in reducing the stressful experience, consequently maintaining people's mental health. In line with this, abundant research has demonstrated the indirect effect of resilience between stress and mental health outcomes such as depression and anxiety ( 7 , 25 ).…”
Section: Introductionmentioning
confidence: 79%
“…When people go through the adversity of COVID-19, resilience may work as a crucial factor in reducing the stressful experience, consequently maintaining people's mental health. In line with this, abundant research has demonstrated the indirect effect of resilience between stress and mental health outcomes such as depression and anxiety ( 7 , 25 ).…”
Section: Introductionmentioning
confidence: 79%
“…Resilience as a coping mechanism is related to protective and risk factors (Kumar et al, 2022 ). Protective factors enable individuals to overcome stressful life events and risks, and risk factors can pose to be harmful to individuals.…”
Section: Review Of Literature and Hypotheses Developmentmentioning
confidence: 99%
“…Although resilience could be considered a protective factor against mental health problems, particularly during this time of health crisis 21 ; however, the role of resilience with respect to stress-related fear and depression due to COVID-19 among healthcare workers remains unknown. Consequently, there is a need to understand the mediating role of resilience in buffering the effects on emotional well-being.…”
Section: Introductionmentioning
confidence: 99%